Note Block Studio: A Music Creation Application for Minecraft Note Block Songs - Costa, Bernardo; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical, 2025)
Note Block Studio (NBS) is an open-source music creation application for desktop computers. It aims to help anyone easily create music for the critically acclaimed video game Minecraft, using blocks that emit musical notes. NBS features an intuitive grid workspace, where a user can arrange musical notes to create songs. These songs can then be exported to a musical circuit, allowing them to be played in-game. Since its first release in 2011, NBS has gathered a vibrant community with tens of thousands of players and musicians. Many software tools and plugins have been developed to enhance the app’s native capabilities, deeply enriching the project’s ecosystem. Moreover, advanced compositional techniques have been created to overcome the limitations of note blocks. These advancements have paved the way for hundreds of musical works, visualizations, and even collaborative pieces to emerge around the app, which have reached millions of players through online social platforms. In this paper, we provide an in-depth analysis of NBS and its features, showcase its community, and present some of the modern initiatives powered by the app. We also explore how its appeal has helped it secure a solid position within Minecraft’s musical community. Finally, we investigate its limitations and potential research paths. Ultimately, our goal is to introduce NBS to the academic community, building a strong contextual foundation to support further development of its ecosystem.